Implementation of Indoor Air Quality Monitoring Systems of Particulate Matter 2.5 Based on the Internet of Things - Irbah, Nafi'atul; Nurika, Globila; Ramani, Andrei (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Indoor air quality significantly influences human health because humans can do work and rest indoors. Particulate Matter (PM2.5) is ranked 5th as the leading risk factor for death in the world and causes more than 103 million disabilities. PM2.5 concentrations are the highest, so a monitoring system is needed that can monitor air conditions in real-time and continuously. Methods: Research was conducted using the Research and Development (R&D) type. The scope of the research method is making prototypes and fieldtesting tools. Determination of field test locations is based on indicators such as (i) inadequate ventilation in the respondent's house so that air circulation does not run well; (ii) The family room and bedroom are close to the kitchen and waste incinerator, which has the potential to produce PM2.5 pollutants. Data analysis used descriptive analysis to get a picture of indoor air quality. Results and Discussion: The designed monitoring system was calibrated with the Air Quality Monitor 8 in 1 PM2.5 tool. The average PM2.5 concentration measurement for 24 hours showed that all test points exceeded the standard limit. Room 3 (family room) had the highest PM2.5 concentration, while room 4 (bedroom) had the lowest PM2.5 concentration. Conclusion: The area of air ventilation, mining activities, mining product transportation activities, the intensity of watering roadsides and home yards, and cooking activities influence PM2.5 concentrations.